2019
DOI: 10.3389/fnbeh.2019.00260
|View full text |Cite
|
Sign up to set email alerts
|

Intersubject Synchronization of Late Adolescent Brain Responses to Violent Movies: A Virtue-Ethics Approach

Abstract: Movies that involve violence increasingly attract large audiences, leading to concern that such entertainment will encourage imitation by youth, especially when the violence is seen as justified. To assess differences between brain responses to justified and unjustified film violence, we computed intersubject correlation (ISC) of fMRI BOLD time courses in a sample of late adolescents while they watched pairs of movie segments featuring violent characters prior to and during violent action. Based on a virtue-et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Accordingly, the sample size we used was an approximate sample needed to achieve a moderate effect (Cohen’s d = 0.5) in this analysis ( Faul et al, 2007 ). Note, that our sample was much larger than was previously used in the ISC fMRI studies ( Jääskeläinen et al, 2016 ; Pollick et al, 2018 ; Adebimpe et al, 2019 ; Leong et al, 2020 ; Sachs et al, 2020 ; Hu et al, 2022 ) and one fNIRS study ( Rowland et al, 2018 ). In addition, for the fMRI data, it has been shown that the sample size of 20 participants was sufficient for high reliability of the effects in the ISC analysis ( Pajula and Tohka, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the sample size we used was an approximate sample needed to achieve a moderate effect (Cohen’s d = 0.5) in this analysis ( Faul et al, 2007 ). Note, that our sample was much larger than was previously used in the ISC fMRI studies ( Jääskeläinen et al, 2016 ; Pollick et al, 2018 ; Adebimpe et al, 2019 ; Leong et al, 2020 ; Sachs et al, 2020 ; Hu et al, 2022 ) and one fNIRS study ( Rowland et al, 2018 ). In addition, for the fMRI data, it has been shown that the sample size of 20 participants was sufficient for high reliability of the effects in the ISC analysis ( Pajula and Tohka, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, violent behavior is often the result of several combined factors, particularly increased amygdala activity due to genetic predisposition and an unfavorable environment during early development, that both lead to decreased activity of brain areas responsible for empathic behavior, primarily the vmPFC and OFC [217]. Watching scenes of unjustified violence in normal individuals activates primarily lateral parts of the OFC (processing the punitive stimuli) and insula (empathizing with the victim), whereas the vmPFC is activated only when watching scenes of self-defense [220]. A correlation was observed between reduced amygdala volume and aggressive, violent, and criminal behavior, along with weaker connectivity between the amygdala and vmPFC and OFC, whose activity was decreased [220].…”
Section: Aggressionmentioning
confidence: 99%
“…Watching scenes of unjustified violence in normal individuals activates primarily lateral parts of the OFC (processing the punitive stimuli) and insula (empathizing with the victim), whereas the vmPFC is activated only when watching scenes of self-defense [220]. A correlation was observed between reduced amygdala volume and aggressive, violent, and criminal behavior, along with weaker connectivity between the amygdala and vmPFC and OFC, whose activity was decreased [220]. Such persons are incapable of empathy, being unscrupulous and egocentric instead, most often narcissistic and manipulative, incapable of loving and truly caring about someone, and also incapable of experiential learning and feeling ashamed, guilty, embarrassed and regretful.…”
Section: Aggressionmentioning
confidence: 99%
See 1 more Smart Citation